2002
DOI: 10.1159/000071040
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic delineation of a deletion of chromosome 13q12→q13 in a patient with autism and auditory processing deficits

Abstract: In a sporadic case of autism and language deficit due to auditory processing defects, molecular genetic studies revealed that a chromosomal deletion occurred in the 13q12→q13 region. No chromosome abnormalities were detected in the parents. We determined that the deletion occurred on the paternally derived chromosome 13. There are two previous reports of chromosome 13 abnormalities in patients with autism. The deletion in the subject described in this paper maps between the two chromosome 13 linkage peaks desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…In a case report regarding autism and language deficits caused by auditory processing defects, Smith et al [42] reported the discovery of a 9-Mb region that was deleted in the 13q12 q13 region of chromosome 13. RGC-32 is one of the 27 genes that mapped within the deleted region, suggesting that it may function in brain development, and particularly in auditory processing.…”
Section: Rgc−32 and Other Diseasesmentioning
confidence: 99%
“…In a case report regarding autism and language deficits caused by auditory processing defects, Smith et al [42] reported the discovery of a 9-Mb region that was deleted in the 13q12 q13 region of chromosome 13. RGC-32 is one of the 27 genes that mapped within the deleted region, suggesting that it may function in brain development, and particularly in auditory processing.…”
Section: Rgc−32 and Other Diseasesmentioning
confidence: 99%
“…auditory behavior ͉ auditory brainstem responses ͉ auditory cortex ͉ autism ͉ language learning impairment C linical and epidemiological studies of language impairment and autism have shown a strong genetic component with multiple genes involved (1)(2)(3). The distributed complex of brain system abnormalities, however, also indicates that exposure to environmental factors at early stages of brain development may be a contributing or even causal factor in a significant percentage of cases.…”
mentioning
confidence: 99%
“…The karyotype of this patient showed a deletion involving 13q13 and portions of q12 and q14 which was not present in an autistic maternal cousin. The deletion in the second patient encompassed a 9Mb fragment in the 13q12-q13 region which was paternally derived [33]. It was not reported whether the father also showed autistic features.…”
Section: The Identification Of Neurobeachin As a Candidate Gene For Amentioning
confidence: 93%
“…1A) [33][34][35]. The initial deletion was described in a woman with autism, sporadic retinoblastoma and a reduced esterase D activity [35].…”
Section: The Identification Of Neurobeachin As a Candidate Gene For Amentioning
confidence: 99%